FACEBOOK AS AN ACTOR - A CASE OF STUDENTS NEGOTIATING THEIR SOCIAL PRESENCE IN AN ONLINE COURSE - Monica Johannesen; Leikny Øgrim; Ole Smørdal (Seminar.net, 2016)
This article reports on a study of a higher education online course based on asynchronous communication. The selection of technology for online discussions aimed at creating a sense of togetherness among the teachers and the students. This choice proved to be a source of insights into the differences of agency of a virtual learning environment (VLE) compared to social media when it comes to social presence. We discuss the agency of Fronter, our formal VLE, and Facebook, when it comes to their effect on the relevant social networks at hand. Important issues identified are related to the quality and nature of the professional and social relations between teachers and students as well as their technology practices in the online course. The discussions are based on the concepts of immediacy and intimacy, as these issues kept appearing in the interviews with the students. The article suggests that the differences of materiality between VLEs and social media, exemplified here by Fronter and Facebook, matter in several respects: how social relations are established and sustained, the agency of the technology in respect to social presence and control and how the technologies affect the quality of dialogic pedagogy.